Surgical Excision of a Hemophilic Pseudotumor Causing Vascular Impingement in a Patient with Severe Hemophilia A: A Case Report - Pradilla, Juan Manuel; Tinoco, Abelardo; Cely, Luis Miguel; Buitrago, Martha Paola (Revista Brasileira de Ortopedia, 2024)
Patients with hemophilia disease have a high risk of hemorrhage. Most hemorrhages can occur in the musculoskeletal system, presenting as hematomas, or, in rare occasions, as hemophilic pseudotumors, an uncommon pathology that are often misdiagnosed as musculoskeletal tumors because of their clinical behavior and characteristics on diagnostic imaging. Despite many treatment options, surgical excision is the treatment of choice. This article describes a case of hemophilia A in a patient who suffered from progressive swelling of the right thigh for 12 months. Diagnostic imaging suggested a hemophilia pseudotumor with vascular bundle impingement. Surgical excision was successful.
Keywords: hematoma; hemophilia A; hemorrhage; musculoskeletal system